1. ## equality trigonometry

Let a, b ≠kπ : $\displaystyle a.sin\alpha a\sin\alpha +b. cos\alpha b\cos\alpha = a.sin\beta a\sin\beta +b. cos\beta b\cos\beta =c$.

Prove: cos^{2}\frac{\alpha- \cos^{2}\frac{\alpha- \beta }{2}=\frac{c^{2}}{a^{2}+b^{2}}.

2. Originally Posted by arm
Let a, b ≠kπ : $a.sin\alpha a\sin\alpha +b. cos\alpha b\cos\alpha = a.sin\beta a\sin\beta +b. cos\beta b\cos\beta =c$.

Prove: $cos^{2}\frac{\alpha- \cos^{2}\frac{\alpha- \beta }{2}=\frac{c^{2}}{a^{2}+b^{2}}$
Hi arm,

When you type Latex commands always use the [ math][ /math] to wrap them.

3. Originally Posted by arm
Let a, b ≠kπ : $\displaystyle a.sin\alpha a\sin\alpha +b. cos\alpha b\cos\alpha = a.sin\beta a\sin\beta +b. cos\beta b\cos\beta =c$.

Prove: cos^{2}\frac{\alpha- \cos^{2}\frac{\alpha- \beta }{2}=\frac{c^{2}}{a^{2}+b^{2}}.
The formatting of what you're trying to prove is unreadable (I am not going to bother editing it to what it should be - you can re-post it in this thread).

To get help you need to show some effort. Show your work and say where you're stuck.